Characteristics of Medical Products Comprising Human Cells, Genes, or Tissues Developed in Japan and the European Union Compared via Public Assessment Reports - Kurauchi, Ryosuke; Kasai, Hiroi; Ito, Tatsuya (Frontiers in Bioengineering and Biotechnology, 2020)
Medical products comprising human cells, genes and tissues have been developed for clinical applications worldwide, and their developmental environment has been established. However, marketing authorization regulations are complicated among regions. The purpose of this study is to identify the characteristics of medical products comprising human cells, genes and tissues. We used website data, books from survey companies, and reports from public agencies to conduct two investigations; a general information survey in 24 countries and individually survey nonclinical and clinical developments of 17 products in Japan and the European Union. The numbers of products used in orthopedic surgery and dermatology have increased since 2000, and the number of hematological products has increased since 2011. Many aspects of clinical and nonclinical development of medical products comprising human cells, genes and tissues differ between Japan and the EU. These results are possible to offer the development processes of medical products comprising human cells, genes and tissues to researchers and clinicians, and like to contribute to facilitate access to new medical products in your research field.